Women in neurosurgery aim for recognition of merit, not tokenism: insights from an Italian survey - Cappelletto, Barbara; Rispoli, Rossella; Peretta, Paola; Valentini, Laura Grazia; Garozzo, Debora; Fornari, Maurizio; Alafaci, Concetta; Diamond, Mathew E. (Frontiers in Surgery, 2025)
The sparse representation of women in neurosurgery, compared to other medical fields, has driven debates about causes and remedies. This study explores gender disparities through a survey of female members of the Italian Society of Neurosurgery (SINch). Comprising 49 questions, the survey focused on career trajectories, work-life balance, mentorship, and perceptions of gender-related challenges. The respondents numbered 119, with 51% from 31 to 40 years old. Personal motivation emerged as the dominant driver for choosing neurosurgery. Mentorship was identified as a critical factor, with 69% perceiving benefits from having female mentors. Over half of respondents reported experiencing gender bias during residency and in the workplace. Many reported facing discouragement from peers and professors. A substantial proportion reported difficulty reconciling family responsibilities with professional duties, with 84% attributing lack of commitment to a relationship, and 49% attributing delayed motherhood, to professional demands. Respondents also expressed dissatisfaction with their visibility in scientific societies and conferences. As a remedy to hindrances of career progression, the majority of respondents do not envision female-centered initiatives (e.g., quotas in scientific societies, “women sections” or “pink rooms” at conferences). Instead, the respondents seek recognition based on merit. Rather than being categorized by their gender, the women surveyed advocate for a fair system where all individuals work on equal footing. Discussing these findings in the context of initiatives entailing quotas and enforced diversity, we argue that identity-based programs undermine core principles. Addressing underrepresentation in neurosurgery requires solutions that promote access and recognition for contributions irrespective of gender. Scientific associations have a fundamental responsibility in combating prejudice and enforcing measures to ensure the elimination of all forms of bias within neurosurgery.